Beyond “Bleeding, Infection, Damage to Surrounding Structures”: Challenges and Opportunities When Communicating about Surgical Risks - Fritz, Melanie L.; De Roo, Ana C. (Clinics in Colon and Rectal Surgery, 2025)
Informed consent and shared decision-making are central tenets of surgical consultations and the decision to proceed, or not, with surgery. These standard practices require communication with patients about the risks and benefits of the procedures they are considering. Yet communicating about risk is not straightforward. Limited health literacy, cognitive pitfalls, and the emotional experience of illness or a new diagnosis can all impact how patients interpret the information they receive. Beyond the legal obligations to ensure patients are informed, communicating effectively about risk can also support patients throughout the perioperative period, particularly if rare complications occur. We propose a framework for discussing risks and downsides of surgery that contextualizes rare risks in the expected trajectory of recovery, supporting patients through the decision-making process and onwards.
Keywords: shared decision-making; communication; informed consent; prognostication